Exploring Teachers' Perspectives on Culturally Responsive Teaching in Stoichiometry Learning Oriented to Green Chemistry - Fitri, Hajidah Salsabila Allissa; Wiyarsi, Antuni; Widarti, Hayuni Retno; Yamtinah, Sri; Pratiwi, Yunilia Nur (Universitas Ahmad Dahlan, 2025)
This study explores high school chemistry teachers’ perceptions of culturally responsive teaching (CRT) in stoichiometry learning with an orientation toward green chemistry principles. CRT provides a framework for integrating local culture, while green chemistry oriented highlights sustainability in learning abstract topics such as stoichiometry. This qualitative descriptive study involved nine Indonesian chemistry teachers selected purposively from active high school chemistry teachers familiar with stoichiometry and green chemistry. Although the sample size was limited, it provided data saturation and in-depth insights from teachers’ experiences. Data were collected through an open-ended questionnaire covering seven aspects, including teachers’ understanding of CRT, integration of local culture and green chemistry orientation in stoichiometry teaching, and perceived needs. Thematic analysis identified six themes related to teaching barriers, instructional practices, teachers’ CRT understanding, cultural integration, green chemistry orientation, and professional development needs. While teachers expressed strong support for CRT with a green chemistry orientation, implementation remains limited by structural and pedagogical constraints. The study underscores the importance of targeted support to empower teachers in fostering culturally responsive and sustainability-oriented chemistry learning, while acknowledging limitations related to the Indonesian context and the potential for social desirability bias in self-reported data.